An update of the effects of vitamins D and C in critical illness - Hill, Aileen; Starchl, Christina; Dresen, Ellen; Stoppe, Christian; Amrein, Karin (Frontiers in Medicine, 2023)
Many critically ill patients are vitamin D and vitamin C deficient and the current international guidelines state that hypovitaminoses should be compensated. However, uncertainty about optimal dosage, timing and indication exists in clinical routine, mainly due to the conflicting evidence. This narrative review discusses both micronutrients with regards to pathophysiology, clinical evidence of benefits, potential risks, and guideline recommendations. Evidence generated from the most recent clinical trials are summarized and discussed. In addition, pragmatic tips for the application of these vitamins in the clinical routine are given. The supplementations of vitamin D and C represent cost-effective and simple interventions with excellent safety profiles. Regarding vitamin D, critically ill individuals require a loading dose to improve 25(OH)D levels within a few days, followed by a daily or weekly maintenance dose, usually higher doses than healthy individuals are needed. For vitamin C, dosages of 100–200 mg/d are recommended for patients receiving parenteral nutrition, but needs may be as high as 2–3 g/d in acutely ill patients.